Review of ISO 45001:2018 Implementation as Prevention Effort from Fire Occurred in PT Pertamina (Persero) Refinery Unit VI Balongan - Yosef Budiman; Niti Bagus Wirotomo; Muhammad Wisnu Prasetio (Jurnal Syntax Admiration, 2024)
Abstract PT Pertamina Refinery Unit VI Balongan has made a significant contribution in providing good income for PT Pertamina and the state. A large number of petroleum processing products produced daily cause a high risk of fire. Fires and explosions at oil refineries are still common even though major oil companies have occupational safety and health systems in place. Monitoring errors and the absence of re-evaluation of established companies for a long time are the reasons why this can happen. This research uses a descriptive approach through literature studies to collect data and obtain the necessary information by studying various journals, conference proceedings, books, and written references. The results of the research were obtained by PT Pertamina Refinery Unit VI Balongan, which applies several rules regarding work safety from ISO 45001: 2018 based on technical and non-technical aspects. In the technical aspect, the rules include the installation of warning signs and signs, noise, temperature, lighting intensity and personal safety equipment. Meanwhile, the regulations include administration and licensing as Safe Work Permits in non-technical aspects. However, based on several parameters of the application of ISO 45001: 2018, aspects that do not meet the standards are found and can be a problem, resulting in the potential for fire. This study concluded that PT Pertamina Refinery Unit VI Balongan must be able to provide firmness in implementing work safety rules or procedures for its employees.